The influence of chronotype on the academic achievement of children and adolescents – evidence from Russian Karelia. Issue 6 (1st November 2016) - Kolomeichuk, Sergey N.; Randler, Christoph; Shabalina, Irina; Fradkova, Ludmila; Borisenkov, Mikhail
Abstract: The inter-individual differences of human time-of-day preferences could divide population into "morning", "intermediate" and "evening" types. This variety of sleep patterns is accompanied by differences in the timing of peak cognitive performance. The morningness–eveningness trait, also known as chronotype, is distributed on a continuum, with unequivocal early morning and night owl types at the opposite extremes of the distribution while most of the population shows an intermediate or neither type weak sleep pattern. Obviously, the discrepancy between biological and the social clocks has a distinct impact on physiological processes in humans with different chronotype. It is known that natural light regime in circumpolar regions influences human performance. Most work focused on the relationship between academic achievement and chronotype in students from middle latitudes. The primary aim of our study is to investigate the relationship between chronotype and academic achievement in schoolchildren (6th–11th grade) from north-west Russia (Russian Karelia). The Munich chronotype questionnaire was used in the study, and all participants were required to answer a question about their school achievement. Early midpoint of sleep and longer average sleep duration were associated with better grades. Large social jetlag was associated with worse grades. In a linear regression, gender was the most important predictor of grades, followed by midpoint of sleep and age. This is the first study that has been carried out among school pupils from Russian Karelia, and it shows that evening orientation linked with poorer academic grades at this high latitude.